Psychomotor and cognitive effects of 15-minute inhalation of methoxyflurane in healthy volunteers: implication for post-colonoscopy care - Nam Q. Nguyen; Jenna Burgess; Tamara L. Debreceni; Leanne Toscano (Endoscopy International Open, 2016)
Background and study aims: Colonoscopy with portal inhaled methoxyflurane (Penthrox) is highly feasible with low sedation risk and allows earlier discharge. It is unclear if subjects can return to highly skilled psychomotor skill task shortly after Penthrox assisted colonoscopy. We evaluated the psychomotor and cognitive effects of 15-minute inhalation of Penthrox in adults. Patients and methods: Sixty healthy volunteers (18 to 80 years) were studied on 2 occasions with either Penthrox or placebo in a randomized, double-blind fashion. On each occasion, the subject’s psychomotor function was examined before, immediately, 30, 60, 120, 180 and 240 min after a 15-minute inhalation of studied drug, using validated psychomotor tests (Digit Symbol Substitution Test (DSST), auditory reaction time (ART), eye-hand coordination (EHC) test, trail making test (TMT) and logical reasoning test (LRT). Results: Compared to placebo, a 15-minute Penthrox inhalation led to an immediate but small impairment of DSST (P < 0.001), ART (P < 0.001), EHC (P < 0.01), TMT (P = 0.02) and LRT (P = 0.04). In all subjects, the performance of all 5 tests normalized by 30 minutes after inhalation, and was comparable to that with placebo. Although increasing age was associated with a small deterioration in psychomotor testing performance, the magnitude of Penthrox effects remained comparable among all age groups. Conclusions: In all age groups, a 15-minute Penthrox inhalation induces acute but short-lasting impairment of psychomotor and cognitive performance, which returns to normal within 30 minutes , indicating that subjects who have colonoscopy with Penthrox can return to highly skilled psychomotor skills tasks such as driving and daily work the same day.